(untitled) (Academicia Globe: Inderscience Research, 2023)
The article discusses the specific features of diseases of the musculoskeletal system and ways to improve the state of the body through exercise therapy. The symptoms of diseases, the causes of their occurrence, statistics on the number of people with a particular musculoskeletal disease by country are given. The essence of exercise therapy is also revealed, the benefits and specifics of exercise therapy for diseases of the musculoskeletal system are described, a number of exercises are given that will improve the physical condition of the patient.